Superhydrophobic magnetic nanoparticle-free fatty acid regenerated from waste cooking oil for the enrichment of carcinogenic polycyclic aromatic hydrocarbons in sewage sludges and landfill leachates. Issue 90 (14th September 2016) - Mahmad Rozi, Siti Khalijah; Bakhshaei, Shabnam; Abdul Manan, Ninie Suhana; Mohamad, Sharifah
Abstract : In this study, Fe3 O4 nanoparticles grafted with superhydrophobic free fatty acids from waste cooking oil (FFA@MNP ) were successfully fabricated as an adsorbent for the magnetic solid phase extraction (MSPE) technique. Abstract : In this study, Fe3 O4 nanoparticles grafted with superhydrophobic free fatty acids from waste cooking oil (FFA@MNP ) were successfully fabricated as an adsorbent for the magnetic solid phase extraction (MSPE) technique. The synthesized nanomaterial (FFA@MNP ) was analyzed using Fourier transform infrared spectroscopy, transmission electron microscopy, X-ray diffraction, energy dispersive X-ray spectroscopy, water contact angle analysis and vibrating sample magnetometry, which confirmed the successful functionalization of free fatty acids onto the surface of Fe3 O4 nanoparticles. The adsorption efficiency of the synthesisedFFA@MNP in MSPE was evaluated by the extraction of five selected polycyclic aromatic hydrocarbons (PAHs), namely, fluorene (Flu), fluoranthene (FLT), pyrene (Pyr), chrysene (Cry), and benzo( a )pyrene (BaP), from environmental samples prior to HPLC-DAD analysis. The MSPE method was optimized for various parameters such as adsorbent dosage, type of organic eluent, volume of organic eluent, extraction time, desorption time, pH of the solution and sample volume. The low detection limit for the proposed MSPE was found to be 0.001 to 0.05 ng mL −1 . Under optimized conditions, the newly synthesized material was applied as an adsorbent for environmental leachate and sludge samples for enrichment of the selected PAHs from these complex matrices. The stability and reusability studies demonstrated thatFFA@MNP could be used for up to five cycles. Due to hydrophobic interactions between the long alkyl chains ofFFA@MNP and PAHs, good recoveries (82.8–116.6%) with low relative standard deviations ranging from 5.2% to 11.0% were obtained for the spiked leachate samples. For the spiked sludge samples, the recovery range was found to be from 72.3% to 119.9%, with a satisfactory % RSD (4.8–11.8%).